Hubungan antara Berat Badan Lahir Bayi dengan Ruptur Perineum pada Primipara - Russiska Russiska; Susan Yuliyantika; Merissa Laora Heryanto (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
The Maternal Mortality Rate (MMR) in Indonesia is around 90% at the time of delivery. in Indonesia until 2018 the Maternal Mortality Rate is still high at 305 per 1000 live births[1]. This is caused by postpartum bleeding due to several factors such as uterine atony and perineal rupture. The research objective was to determine the relationship between birth weight of infants and perineal rupture in Primipara at Japara Public Health Center, Kuningan Regency in 2019. The research method was analytic with a cross sectional approach, sampling with a total sampling technique with a total of 52 mothers giving birth. The instrument used was a checklist sheet and the analysis used Spearman Rank. Based on the results of the univariate analysis study, most mothers gave birth to babies with normal birth weight, namely around 59.6%, while most of the mothers experienced perineal rupture, namely around 51.9%. The results of the bivariate analysis showed a value (p = 0.09), this indicated that there was a significant relationship between birth weight of infants and perineal rupture in mothers who gave birth. It was concluded that there was a significant relationship between birth weight of infants and perineal rupture in mothers who gave birth. It is hoped that midwives will always carry out labor management in accordance with the standards of normal delivery care when giving birth and teach pregnant women how to massage the perineum.